Groundwater quality assessment and application of multivariate statistical analysis in Luvuvhu catchment, Limpopo, South Africa. (November 2020) - Elumalai, Vetrimurugan; Nethononda, Vhonani G.; Manivannan, V.; Rajmohan, N.; Li, Peiyue; Elango, L.
Abstract: Groundwater quality and its suitability for drinking and irrigation uses were assessed and multivariate statistical analysis were applied to understand the chemical characteristics of groundwater in the upper part of Luvuvhu sub-catchment in Limpopo, South Africa. The groundwater samples collected during August 2015 (n = 41) and November 2016 (n = 40) were analysed for chemical constituents. The groundwater is fresh and acidic to alkaline in nature. The major hydrochemical facies are Ca–Mg–Cl and Ca–HCO3 - in the study area. Groundwater suitability assessment for drinking purposes carried out using World Health Organisation and South African National Standards suggest that groundwater is suitable for drinking without any restrictions. Irrigation suitability assessment suggested that groundwater is suitable for all types of crops and soils. Pearson correlation analysis and principle component analysis (PCA) explains that groundwater chemistry is governed by natural and anthropogenic activities. Hierarchical cluster analysis (HCA) classified wells into three groups (CG1, CG2, CG3). Wells in CG1 and CG2 are less mineralized and are of Ca–Mg–Cl water types. Water chemistry in these wells are affected by recharge process and surface contamination sources. Wells in CG3 are highly mineralized and are of Ca–HCO3 type. Bicarbonate is the dominant anion and water chemistry in CG3 is regulated by silicate and carbonate weathering processes. This study recommends further periodic monitoring to protect aquifers in long run. Highlights: PCA analysis indicates that groundwater is contaminated by geogenic (weathering of minerals) and anthropogenic (agricultural activities) sources. HCA- CG1 and CG2 clusters are less mineralized and has sources from surface contamination and recharge process. HCA- CG3 was highly mineralized and has sources from silicate and carbonate weathering. This study recommends further periodic monitoring to protect the aquifer in long run.